2021
DOI: 10.1021/acs.jpcb.1c05117
|View full text |Cite
|
Sign up to set email alerts
|

Ion Pairing of the Neurotransmitters Acetylcholine and Glutamate in Aqueous Solutions

Abstract: Neurotransmitters (NTs) play an important role in neural communication, regulating a variety of functions such as motivation, learning, memory, and muscle contraction. Their intermolecular interactions in biological media are an important factor affecting their biological activity. However, the available information on the features of these interactions is scarce and contradictory, especially, in an estimation of possible ion binding. In this paper, we present the results of a study for two well-known NTs, ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
11
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 106 publications
4
11
3
Order By: Relevance
“…Namely, the 3DRISM reduces the problem to numerical solution of Ornstein-Zernike integral equations similar to those for simple fluids. The model is very popular for treatment of small bio-rganic solutes [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the 3DRISM reduces the problem to numerical solution of Ornstein-Zernike integral equations similar to those for simple fluids. The model is very popular for treatment of small bio-rganic solutes [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…They aim to determine the reactive sites of ACh conformers, [28] the conformational changes' pathway, [29] the fluorination effect to conformational changes, [30] hydration features, [31] and the features of ACh conformers paired to ions in biological media. [32] In our previous work, we demonstrated that two groups of ACh conformers, capable of undergoing hydrolysis without being preceded by conformational changes, have an energy difference of 8 kcal/mol. [33] Therefore, to verify the nonenzymatic hydrolysis contribution towards ACh depletion, we investigate the conformational effect on ACh neutral (nonenzymatic) hydrolysis in aqueous solution.…”
Section: Introductionmentioning
confidence: 93%
“…In recent decades, computational studies on ACh conformational properties in aqueous solution have dominated. They aim to determine the reactive sites of ACh conformers, [28] the conformational changes’ pathway, [29] the fluorination effect to conformational changes, [30] hydration features, [31] and the features of ACh conformers paired to ions in biological media [32] . In our previous work, we demonstrated that two groups of ACh conformers, capable of undergoing hydrolysis without being preceded by conformational changes, have an energy difference of 8 kcal/mol [33] .…”
Section: Introductionmentioning
confidence: 99%
“…Organic ions, which are readily soluble in water, are usually studied: guanidinium and arginine ions [ 1 , 2 , 3 ], protonated acridine cations [ 4 ], etc. [ 5 , 6 ]. The driving force of the aggregation of identically charged organic ions in aqueous solutions is solvation free energy arising from the adaptation of the hydrogen bond (H-bond) network of water to the solute [ 7 ].…”
Section: Introductionmentioning
confidence: 99%